1963
DOI: 10.1111/j.1438-8677.1963.tb00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Observations in Relation to the Taxonomy of the Orchids of the Netherlands

Abstract: The Orchids in the Netherlands have been subjected to a cytological investigation. The division of the genera Orchis (L.) Klinge into two new genera: Orchis (L.) Vermln. and Dactylorchis (Kl.) Vermln. (Vermeulen, 1947), could be confirmed. In Listera ovata (L.) R. Br. the diploid chromosome number is 34. Deviating numbers 2n = 35 and 2n = 36 were counted. Because aberations in chromosome number do not cause morphological differences these aberations seem to be unimportant. Out of the material investigated it m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
4

Year Published

1965
1965
2000
2000

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 13 publications
3
12
0
4
Order By: Relevance
“…in Aiton fil. showed 2n=38 chromosomes in agreement with previous reports (Kliphuis 1963, Meili-Frei 1966. Also 2n=36 and 42 chromosomes have been observed (Mehra and Kashyap 1983).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…in Aiton fil. showed 2n=38 chromosomes in agreement with previous reports (Kliphuis 1963, Meili-Frei 1966. Also 2n=36 and 42 chromosomes have been observed (Mehra and Kashyap 1983).…”
Section: Resultssupporting
confidence: 82%
“…ex Aiton fil. The observed chromosome number of 2n=34 in all individuals from different localities, coincides with previously reported data (Kliphuis 1963, Meili-Frei 1966, Scrugli 1980, moreover examination of metaphase I in embryo sac mother cells revealed 17 bivalents. Some authors reported different chromosome numbers, i.e.…”
Section: Resultssupporting
confidence: 78%
“…Comme cela a été signalé par différents au· teurs (Kliphui,. ;, 1963et Meili-Frei, 1965, le caryogramme présente une paire de chromol-\Ome:> longs (6 à 7 J.l) acrocentriques. (L.) Chev.…”
Section: -unclassified
“…Mis à part les tables ré-capitulatives d'auteurs tels que Tischler (1950), Love et Love (1961), Fedorov (1974, Ornduff (1967Ornduff ( , 1968 et Moore (1973Moore ( , 1974Moore ( , 1977, seules quelques publications comportent l'étude caryologique d'un nombre important de taxons. Citons : Gadella et Kliphuis (1963) et Kliphuis (1963) pour des espèces prélevées en Hollande, Mehra et Pal (1961), Mehra et Bawa (1962, Mehra et Vij (1972), pour celles de l'Himalaya, Love et Kjellquist (1973) pour les populations du sud de l'Espagne (S 0 de Cazorla et de Albaracin), Scrugli (1977Scrugli ( , 1978Scrugli ( , 1980Scrugli ( , 1981, Scrugli et coll. (1976) et Del Prete (1977 pour les populations italiennes et sardes.…”
Section: Introductionunclassified
“…Skalinska, 1950, Skalinska et al, 1957, 1959, 1961Sweden, Skåne: Lövkvist, 1962 (Kliphuis, 1963). ( M e a s u r e m e n t s …”
mentioning
confidence: 99%